Minimal surfaces in three dimensional Lorentzian Heisenberg group - Turhan, Essin; Altay, Gulden (Springer Heidelberg, 2014)
In this paper, we study the minimal and maximal surface in three dimensional Lorentzian Heisenberg group Heis(3). We obtain characterizations of the one parameter subgroups in three dimensional Lorentzian Heisenberg group which is endowed with left invariant Lorentz metrics g(1), g(2), g(3).
Keywords: Heisenberg group; One parameter subgroup; Minimal surface; Maximal surface